Human Polymerase δ-Interacting Protein 2 (PolDIP2) Inhibits the Formation of Human Tau Oligomers and Fibrils - Kasho, Kazutoshi (Int J Mol Sci, 2021)
A central characteristic of Alzheimer’s disease (AD) and other tauopathies is the accumulation of aggregated and misfolded Tau deposits in the brain. Tau-targeting therapies for AD have been unsuccessful in patients to date. Here we show that human polymerase δ-interacting protein 2 (PolDIP2) interacts with Tau. With a set of complementary methods, including thioflavin-T-based aggregation kinetic assays, Tau oligomer-specific dot-blot analysis, and single oligomer/fibril analysis by atomic force microscopy, we demonstrate that PolDIP2 inhibits Tau aggregation and amyloid fibril growth in vitro. The identification of PolDIP2 as a potential regulator of cellular Tau aggregation should be considered for future Tau-targeting therapeutics.